2022
DOI: 10.1111/apps.12395
|View full text |Cite
|
Sign up to set email alerts
|

Too much of a good thing? Curvilinear effect of instrumental social support on task performance via work engagement

Abstract: Based on the Threat‐to‐Self‐Esteem (TSE) model integrated with the Conservation of Resources (COR) theory, we proposed an inverted U‐shaped curvilinear relationship between receiving instrumental social support and task performance, mediated by work engagement. Further, grounded on the TSE model, we proposed the provision of instrumental social support neutralises the curvilinear association between receiving instrumental social support and work engagement. We examined these hypotheses using two samples of Sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 74 publications
1
11
0
Order By: Relevance
“…Considering the nature of the data, with three levels in which followers completing the questionnaires for approximately ten consecutive days are nested within their leader, the I first calculated intra-class correlation coefficients (ICC) of all variables. The results (Table 2) indicated that ICCs of all variables were higher than the standard suggested by previous researchers (Yang and Diefendorff, 2009;Yun and Beehr, 2023b). Specifically, the percent of variance of instrumental leadership style at individual level (Level 2) was 85.1% and that of transformational leadership style was 65.1%, thus these leadership variables (i.e.…”
Section: Data Analytic Strategiesmentioning
confidence: 65%
“…Considering the nature of the data, with three levels in which followers completing the questionnaires for approximately ten consecutive days are nested within their leader, the I first calculated intra-class correlation coefficients (ICC) of all variables. The results (Table 2) indicated that ICCs of all variables were higher than the standard suggested by previous researchers (Yang and Diefendorff, 2009;Yun and Beehr, 2023b). Specifically, the percent of variance of instrumental leadership style at individual level (Level 2) was 85.1% and that of transformational leadership style was 65.1%, thus these leadership variables (i.e.…”
Section: Data Analytic Strategiesmentioning
confidence: 65%
“…Together, these three indices justify the aggregating approach because the indices are higher than the traditional standard recommended by previous researchers (e.g. Yang and Diefendorff, 2009;Yun and Beehr, 2023a). Thus, following the previous researchers' approach (Chiu et al, 2021), the current study used a 2-2-2 level approach by using the PROCESS macro with bootstrapping (10,000 samples) in SPSS (Hayes, 2017).…”
Section: Data Analytic Strategymentioning
confidence: 91%
“…However, given the data were collected by the organization, there were concerns with voluntariness and anonymity of participants (e.g. Yun & Beehr, 2022). Following the first author's advice, the organization notified all field workers that they are looking for voluntary participants to complete two daily surveys for two consecutive weeks (eight work days, excluding weekends and national holidays) whom the organization would compensate with 100,000 Korean Won (approximately 80 US dollars).…”
Section: Methodsmentioning
confidence: 99%